Mediation at the Holocaust Memorial in Berlin - Dekel, I. author. aut Link
XII, 208 p.
Keywords: Analyzing action at the Holocaust memorial in Berlin, this first ethnography of the site offers a fresh approach to studying the memorial and memory work as potential civic engagement of visitors with themselves and others rather than with history itself.